2017
DOI: 10.3928/00989134-20170707-04
|View full text |Cite
|
Sign up to set email alerts
|

Socially Assistive Robots: Measuring Older Adults' Perceptions

Abstract: To address manpower shortages, health care leaders recommend technology, including robots, to facilitate and augment processes for delivery of efficient, safe care. Little is known regarding older adults’ perceptions of socially assistive robots (SARs). Using the Unified Theory of Acceptance and Use Technology framework, a survey was developed and tested for capturing older adults’ likelihood to use SARs. The Robot Acceptance Survey (RAS) comprises three subscales: Performance Expectancy, Effort Expectancy, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(42 citation statements)
references
References 24 publications
2
40
0
Order By: Relevance
“…A total of 12 studies were included in our analyses: 6 mixed-method, non-randomised user experience trials30–35; 2 pre-post experimental surveys36 37; 1 mixed-method, longitudinal experience trial38; 2 post-experimental surveys39 40; and 1 ethnographic study41 (see Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 12 studies were included in our analyses: 6 mixed-method, non-randomised user experience trials30–35; 2 pre-post experimental surveys36 37; 1 mixed-method, longitudinal experience trial38; 2 post-experimental surveys39 40; and 1 ethnographic study41 (see Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies had no comparator and no baseline 30–35 38 40 41. Additional methodological limitations affecting the non-randomised, quasi-experimental design of the studies were: very small samples’ sizes, with only one study involving more than 100 participants38; and self-reported measures,30 34–37 39 40 not always in combination with observation and/or data retrieved from the robot 31–33 38. Seven studies33–35 37 38 40 41 used validated instruments informed by existing theoretical models44–47; two studies reported the drop-out rate but did not mention the handling of missing data 32 37.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that prior experience with robots leads to higher levels of trust and more positive attitudes towards social robots [48][49][50][51][52]. In an experiment measuring older adults' acceptance of the social robot, NAO, participants tended to be neutral in their perceptions of NAO prior to interactions, but statistically significantly more positive after 30-60 min sessions with NAO [53]. However, this tendency of acceptance of a social robot may vary depending on the generation of users.…”
Section: Effects Of Physical Appearance Of Robotsmentioning
confidence: 99%